Low threshold optical bistability and superluminal light propagation using a dielectric slab via inter-dot tunneling. (10th March 2015) - Taherzadeh, S; Nasehi, R; Mahmoudi, Mohammad
Abstract: The optical bistability (OB) behavior of a dielectric slab doped with quantum dot (QD) molecules is investigated in the presence of the inter-dot tunneling effect. It is shown that the threshold point of OB reduces by increasing inter-dot tunneling as well as by reducing the slab thickness. It is worth noting that the threshold of OB in a slab doped with QD molecules is smaller, by at least one order of magnitude, in respect to free QD molecules. We find that the inter-dot tunneling induces a negative group delay to the reflected pulse and it propagates in the superluminal region. Such simple control can be used in all optical switching.